Proceedings of the 3rd Workshop on Advanced Research and Technology in Industry (WARTIA 2017) 2017
DOI: 10.2991/wartia-17.2017.51
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Titanium Alloys through Molten Salt Electrolysis of Solid Oxides for Medical Implants

Abstract: Abstract:A simple, cost-efficient, energy-saving, electrochemical process is developed to synthesize the biomedical Ti-based metal-containing Group VB (V, Nb, Ta) implant materials in the small size at 900 ºC. The anhydrous CaCl 2 and solid oxides were used as the salt melt medium and raw reactants, respectively. The mechanism of the reduction process was discussed by constant cell voltage electrolysis of different time periods. The as-prepared samples, such as Ti-12.5Zr-2.5Nb-2.5Ta, were characterized by SEM,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Numerous titanium-based alloys and intermetallics such as Ti-10 W, Ti-Si, Nb-10Hf-1Ti, Ti-Nb, Ti-5Ta-2Nb, Ti-6Al-4V, Ti-Nb-Sn, Ti-12.5Zr-2.5Nb-2.5Ta, Ti-15Mo, and high entropy alloys, such as TiNbTaZr, TiNbTaZrHf have been synthesized using the FFC Cambridge process. [31][32][33][34][35][36][37][38][39][40] In the case of the Ti-Cr-V family, vanadium-rich V-4Cr-4Ti alloy has been directly prepared electrochemically from the oxides mixture of V 2 O 3 -Cr 2 O 3 -TiO 2 in the molten CaCl 2 -NaCl eutectic at 800 °C. 41 The study reported the influence of cell voltage, sintering temperature, and electrolysis time on the reduction process during the formation of V-4Cr-4Ti alloy.…”
mentioning
confidence: 99%
“…Numerous titanium-based alloys and intermetallics such as Ti-10 W, Ti-Si, Nb-10Hf-1Ti, Ti-Nb, Ti-5Ta-2Nb, Ti-6Al-4V, Ti-Nb-Sn, Ti-12.5Zr-2.5Nb-2.5Ta, Ti-15Mo, and high entropy alloys, such as TiNbTaZr, TiNbTaZrHf have been synthesized using the FFC Cambridge process. [31][32][33][34][35][36][37][38][39][40] In the case of the Ti-Cr-V family, vanadium-rich V-4Cr-4Ti alloy has been directly prepared electrochemically from the oxides mixture of V 2 O 3 -Cr 2 O 3 -TiO 2 in the molten CaCl 2 -NaCl eutectic at 800 °C. 41 The study reported the influence of cell voltage, sintering temperature, and electrolysis time on the reduction process during the formation of V-4Cr-4Ti alloy.…”
mentioning
confidence: 99%